2009
DOI: 10.1016/j.jfms.2008.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Potentially Pathogenic Enteric Organisms in Clinically Healthy Kittens in the UK

Abstract: Faecal samples were collected from 57 clinically healthy kittens presented for initial vaccination, in the UK. Routine bacteriological examination identified Salmonella species in one and Campylobacter species in five samples. Polymerase chain reaction (PCR) detected the presence of Campylobacter species in a further four samples. Routine parasitological examination revealed Toxocara species ova in nine (including four kittens stated to have been administered an anthelmintic) and Isospora species in four sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…There was little relationship between fecal consistency and the presence of one or more enteropathogens, a finding that has been documented in previous studies (Hill et al, 2000;Vasilopulos et al, 2006;Gow et al, 2009;Queen et al, 2012;Sabshin et al, 2012;Paris et al, 2014;Little et al, 2015;Silva and Lobato, 2015). Although the pathogens evaluated in this study can be associated with gastrointestinal disease, it is apparent that the mere presence of these agents does not consistently result in diarrhea.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…There was little relationship between fecal consistency and the presence of one or more enteropathogens, a finding that has been documented in previous studies (Hill et al, 2000;Vasilopulos et al, 2006;Gow et al, 2009;Queen et al, 2012;Sabshin et al, 2012;Paris et al, 2014;Little et al, 2015;Silva and Lobato, 2015). Although the pathogens evaluated in this study can be associated with gastrointestinal disease, it is apparent that the mere presence of these agents does not consistently result in diarrhea.…”
Section: Discussionsupporting
confidence: 46%
“…Causes of diarrhea include factors such as stress, dietary change, microbiome dysbiosis (Suchodolski et al, 2015), and infectious enteropathogens. A variety of feline and zoonotic enteropathogens capable of inducing diarrhea have been documented in unowned cats (Hill et al, 2000;Spain et al, 2001;Mekaru et al, 2007;Gow et al, 2009;Weese, 2011;Sabshin et al, 2012;Spada et al, 2013;Raab et al, 2016). Factors that affect transmission of enteropathogens include single vs. group housing, sanitation practices, facility construction, preventive health protocols, host immunity, and the prevalence of other infectious organisms (Pedersen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of Campylobacter spp. in pets is variable, ranging in dogs from 4.81% (Andrzejewska et al, 2013) to 87% (Acke et al, 2006) and in cats from 8.7% (Gow et al, 2009) to 75% (Acke et al, 2006). Dogs and cats are considered subclinical hosts of Campylobacter spp., carrying mainly C. upsaliensis, C. jejuni and C. helveticus (Wieland et al, 2005;Workman et al, 2005;Acke et al, 2006Acke et al, , 2009aAcke et al, , 2009bRossi et al, 2008;Parsons et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Anti- Cryptosporidium IgG, IgM and IgA antibodies were detected in 192 (74 per cent), 84 (33 per cent) and 67 (26 per cent) on 258 cats (Mtambo and others 1995). Recently, Cryptosporidium oocysts were not detected in 57 healthy kittens in Scotland (Gow and others 2009). Another study reported a 1 per cent prevalence rate (13 of 1355) in cats with gastrointestinal disease from the UK, the Isle of Man and the Channel Islands (Tzannes and others 2008).…”
mentioning
confidence: 99%